Does the Marriage Tax Differential Influence Same‐Sex Couples' Marriage Decisions?. Issue 1 (3rd November 2020) - Cheng, Christine; Crumbley, D. Larry; Enis, Charles; Yurko, Amy J. N.; Yurko, Joseph P.
Abstract: Objective: This article evaluates whether the federal marriage tax penalty (penalty) or federal marriage bonus (bonus) affects the marriage decisions of same‐sex couples (SSCs). Background: Extant studies provide limited, mixed evidence that the penalty has a nominal economic effect on different‐sex couples' marriage decisions. No evidence exists indicating that the marriage bonus impacts couples' marriage decisions. We use the 2013 federal recognition of same‐sex marriage (SSM) to explore whether the penalty or bonus influences SSCs' marriage decisions. Method: To examine the penalty or bonus influence, a difference‐in‐differences regression compares how the 2013 federal recognition of SSM (which imposes the penalty on SSCs) influenced the marriage–penalty and marriage–bonus relation for SSCs. We obtain household level data for 2012–2016 from American Community Survey's Public Use Microdata Sample and use the National Bureau of Economic Research tax simulation model to estimate each household's penalty or bonus. Results: Our evidence indicates that the penalty is negatively related to SSCs' marriage decisions only after 2013. Overall, a 1% increase in the penalty as a percentage of household income reduces the odds of marriage by up to 6.41%. In contrast, we do not find consistent evidence that the bonus effectively encourages marriage. Conclusion: Our results indicate that only the marriage tax penalty has an economically significant effect on SSCs' marriage decisions.